Do we know the true mechanism of action of the DPP‐4 inhibitors? - Andersen, Emilie S.; Deacon, Carolyn F.; Holst, Jens J. (Diabetes, obesity & metabolism, 2018)
The prevalence of type 2 diabetes is increasing, which is alarming because of its serious complications. Anti‐diabetic treatment aims to control glucose homeostasis as tightly as possible in order to reduce these complications. Dipeptidyl peptidase‐4 (DPP‐4) inhibitors are a recent addition to the anti‐diabetic treatment modalities, and have become widely accepted because of their good efficacy, their benign side‐effect profile and their low hypoglycaemia risk. The actions of DPP‐4 inhibitors are not direct, but rather are mediated indirectly through preservation of the substrates they protect from degradation. The two incretin hormones, glucagon‐like peptide‐1 and glucose‐dependent insulinotropic polypeptide, are known substrates, but other incretin‐independent mechanisms may also be involved. It seems likely therefore that the mechanisms of action of DPP‐4 inhibitors are more complex than originally thought, and may involve several substrates and encompass local paracrine, systemic endocrine and neural pathways, which are discussed here.